Implementasi Peraturan Daerah Kabupaten Madiun Tentang Pengelolaan Sampah - Taufiq Yuli Purnama; Sarjiyati; Yuni Purwati; Yusril Abdul Aziz (Universitas Merdeka Madiun, 2024)
-The Purpose of this study find out the implementation of the Madiun Regency regional regulation on Waste Management, waste management related to the environment is a shared responsibility between the local government and the community, the active role of the community is needed in the implementation of this policy. The method that the author uses in this research is empirical legal research using primary data sources, namely the results of direct interviews with staff of the Madiun Regency Environmental Service and secondary data in this study are laws and regulations. The results of the research and discussion show that the implementation of this regional regulation has been carried out. The Madiun District Environmental Service actively conducts socialisation, training and direction related to waste management, the waste bank program in collaboration with Pegadaian is one of the collaborations that support management and economic improvement. Supporting the implementation of this regional regulation is community participation in assisting the implementation of government policies, especially in the field of waste management, which has an impact on the environment, especially Madiun district.